Plaque Assay for Pneumonia Virus of Mice - Shimonaski, Gerard (1970)
A plaque assay for the quantitation of pneumonia virus of mice is described. To obtain reproducible plaque formation, proteolytic enzymes had to be incorporated in the overlay medium. The plaque morphology observed in the presence of pancreatin and chymotrypsin was superior to that seen with trypsin. Although the plaque assay was found to be slightly less sensitive than the TCID(50) determination described by Harter and Choppin, it enables cloning of the virus by plaque selection and permits further study of pneumonia virus of mice.